Obsolescência planejada: a produção tecnológica como instrumento de repressão social em Herbert Marcuse - Oliveira, Fernando Honorato de (2018)
Research on Herbert Marcuse's approaches to the planned obsolescence of consumer goods in his philosophical production. The reference book for this work is The Unidimensional Man, although several other texts of Herbert Marcuse, before and after the book cited, have been used. The research investigates the impacts of the planned obsolescence on the capitalism of the advanced industrial society, through mechanisms of coercion and social repression that use technological production and psychological induction as tools. The research considers consumption and waste as constitutive elements of this process, using theoretical references developed by Herbert Marcuse, from his reading of Max Weber, Karl Marx, Sigmund Freud and commentators of these authors. The approach of the topic considers that, although Marcuse did not detail the concept of planned obsolescence, this concept is important in the constitution of his critique to modern industrial capitalist society, that needs to maintain the market and the consumption to guarantee the profit. The paper also addresses Marcuse's reading of Freudian concepts and the uses that advanced capitalism makes of these concepts to impose and maintain planned obsolescence. All the theoretical references used are based on the work of Herbert Marcuse, his commentators and some of the authors quoted in his philosophical production, whose terms are related to the object of this research. The conclusions of this paper aim to demonstrate that the advanced industrial society’s capitalism depends on a technical combination of factors, determined by Marcuse, for the capitalist structure to be maintained. Maintaining this structure perpetuates profit through social repression, inducing society to produce, waste and consume what it does not need.